SAT0224 Anti-Tnf Drug Survival in Axial Spondylarthritis is not Related to the New Asas Classification Criteria. (23rd January 2014) - Zufferey, P.; Ghosn, J.; Finckh, A.; Fabreguet, I.; Aubry-Rozier, B.; Dudler, J.; Neto, D.; So, A.
Abstract : Background: Several sets of diagnostic and classification criteria for axial spondyloarthritis (SpA) are currently in use. Some, such as the ESSG criteria cover the entire spectrum of spondyloarthropathies, but may be not sufficiently specific. Biological treatments have proven to be very effective in the relief of symptoms of classic SpA. The new Assessment of Spondyloarthritis international Society (ASAS) classification criteria aim to define more precisely people who might benefit from these new treatments. In Switzerland, undifferentiated SpA patients, who may or may not fulfill the new ASAS classification criteria can receive biologics. Objectives: The primary goal was to compare the efficacy of biologic treatments between patients who met the ASAS criteria for SpA and those who did not match these classification criteria, by analyzing the retention rate of biologic treatments at 12 and 24 months. The secondary objectives were to compare the demographic and clinical data between 2 groups and finally to look for predictive factors of better treatments survival. Methods: A retrospective cohort from a single center included 226 patients with inflammatory back pain fulfilling ESSG criteria and who were seen between September 2011 and September 2012. For 194 patients, data were sufficient to apply the ASAS criteria. ASAS- status was established when both MRI and HLA-B27 data were available. 147 (75%) had at least one biological treatment. Comparison of baseline data between ASAS+/ASAS- patients treated by biologics was done using nonparametric tests. Kaplan–Meier plots, log rank tests and multivariate Cox regression analysis were used to analyze drug retention of biotherapies. The analysis was adjusted for potential confounders, such as CRP (less or more 10 mg/l), gender, duration of symptoms (more or less than 2 years), types of anti-TNF. Results: 111 patients met the ASAS criteria (ASAS+) and 36 patients with were classified as ASAS-. Patients in the two groups (ASAS+/ASAS-) differed by the median age at diagnosis: 30/42 years p<0.0001, mean duration of symptoms at first biologic: 166/83 months p<0.0001, median date of diagnosis: 2006/2009, p<0.0001, presence of uveitis: 25/8%, p=0.0006 and positive family history: 35/7%, p=0.0042 and by the frequency of MRI axial involvement: 76/25% p <0.0001 and HLAB27+: 65/5% p< 0.0001. In the two groups, there was a slight predominance of women: 56/61% and the mean baseline BASDAI at initiation of biologics was similar: 5.8/6.4. The drug retention was parallel and similar in the two groups at 1 and 2 years. It remained similar when treatment discontinuation due to lack of efficacy was analyzed. After multivariate Cox regression analysis only an elevated CRP (>10mg/l) on starting biologic therapy proved to be predictive of better drug survival at 1 and 2 years: Hazard ratio, 7.8 (4.4 - 14.5), p <0.001 in both ASAS+ and ASAS– patients, Conclusions: in this single center cohort, we did not find any difference in drug survival of biologic agents between patients with axial SpA fulfilling or not the new ASAS classification criteria. Our results also suggest that the presence of inflammation is better predictor of longer treatment survival than baseline classification criteria. Disclosure of Interest: None Declared